Comparative Study of Cyberloafing Outcomes in Male and Female Employees - Sijabat, Rauly (Universitas Negeri Semarang, 2021)
Cyberloafing is a new organizational behavior triggered by increasingly easy internet access as a form of using internet facilities provided by companies that have no relevance to work matters. Previous studies have attempted to map variables that can explain cyberloafing even though the results are not yet conclusive. However, empirical testing on cyberloafing outcomes has not been carried out. This study developed a comprehensive research model by testing the variables at the organizational level and the individual level as independent variables as well as conceptualizing and empirically testing cyberloafing outcomes. Model testing was conducted on respondents obtained from several industries engaged in the automotive, education, banking, garment and pharmaceutical sectors using the SEM approach. The results of overall model test showed that there was a real effect of job characteristics, work stress and self-control in explaining cyberloafing. Furthermore, this study also found that cyberloafing could trigger creativity and laziness in employees. However, comparative testing based on gender showed that in male employees, cyberloafing was only explained by work stress while in female employees cyberloafing was explained by job characteristics. Outcome from cyberloafing was only obtained for female employees where cyberloafing could increase the creativity of female employees.